Evaluation of the Potential Seed Dispersal Effectiveness of Malus sieversii (Lebed.) M. Roem. by Cattle - Shilin Bai; Jiang Xu; Yaya Lv; Xiaojun Shi; Dunyan Tan (Diversity, 2023)
The success of plant reproduction is highly dependent on effective seed dispersal. This study aimed to evaluate the potential seed dispersal effectiveness of cattle for Malus sieversii. The impact of cattle on the dispersal quantity and dispersal quality of M. sieversii seeds was explored based on camera trapping, GPS tracking, and germination trials. The results showed that, on average, cattle visited M. sieversii trees 477.33 times during a two-month observation period. Out of these visits, 315 were specifically for fruit removal. The fruit removal rate per cattle visit was as high as 96.67%. Additionally, cattle were able to disperse M. sieversii seeds up to a maximum distance of 533.67 m, with an average dispersal distance of 134.62 m. The average distance of cattle movement was recorded as 176.95 m/h, with peak activity observed during 11:00–13:00 and 19:00–21:00. The germination rate of M. sieversii seeds that passed through the digestive tract of cattle was significantly higher than that of control seeds. Finally, the emergence rate and survival rate of seeds dispersed by cattle to forest edges and gaps were significantly higher than those dispersed to understory. These findings suggest that cattle can serve as effective long-distance dispersers of M. sieversii seeds and may play a crucial role in the regeneration and expansion of M. sieversii populations in the Ili Botanical Garden.